Direct Torque Control Induction Motor Drive with Improved Flux Response. (10th September 2012) - Singh, Bhoopendra; Jain, Shailendra; Dwivedi, Sanjeet
Abstract : Accurate flux estimation and control of stator flux by the flux control loop is the determining factor in effective implementation of DTC algorithm. In this paper a comparison of voltage-model-based flux estimation techniques for flux response improvement is carried out. The effectiveness of these methods is judged on the basis of Root Mean Square Flux Error (RMSFE), Total Harmonic Distortion (THD) of stator current, and dynamic flux response. The theoretical aspects of these methods are discussed and a comparative analysis is provided with emphasis on digital signal processor (DSP) based controller implementation. The effectiveness of the proposed flux estimation algorithm is investigated through simulation and experimentally validated on a test drive.